2014
DOI: 10.1186/1746-1596-9-62
|View full text |Cite
|
Sign up to set email alerts
|

A case report of seronegative cat scratch disease, emphasizing the histopathologic point of view

Abstract: Cat scratch disease, necrotizing granulomatous lymphadenitis caused by Bartonella henselae, usually benign and self-limited. However, various clinical manifestations and no pathognomonic histopathologic features can lead to misinterpretations and diagnostic disputes. We report a case of cat scratch disease in a 39-yr-old male patient with fever and left axillary lymphadenitis. He had a history of cat bite on the left hand dorsum. On excision, the lymph node showed follicular hyperplasia, stellate microabscesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Physicians are familiar with cat scratch disease (CSD), a benign self-limiting infection that generally resolves spontaneously without the need for antibiotic administration. 19 In contrast to classical CSD, recent evidence indicates that B henselae , the primary or sole cause of CSD, can be isolated from the blood of healthy blood donors, 20 at-risk animal health workers, 9 , 10 and patients with rheumatologic 21 - 23 and neuropsychiatric symptoms. 4 , 5 Proving disease causation for stealth pathogens, such as Bartonella spp., is challenging 24 and a One Health approach 16 has been proposed to more effectively characterize the comparative medical importance of this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians are familiar with cat scratch disease (CSD), a benign self-limiting infection that generally resolves spontaneously without the need for antibiotic administration. 19 In contrast to classical CSD, recent evidence indicates that B henselae , the primary or sole cause of CSD, can be isolated from the blood of healthy blood donors, 20 at-risk animal health workers, 9 , 10 and patients with rheumatologic 21 - 23 and neuropsychiatric symptoms. 4 , 5 Proving disease causation for stealth pathogens, such as Bartonella spp., is challenging 24 and a One Health approach 16 has been proposed to more effectively characterize the comparative medical importance of this genus.…”
Section: Discussionmentioning
confidence: 99%
“…On color Doppler, these masses typically demonstrate hila with vascular flow consistent with enlarged intramammary lymph nodes. Biopsy may be necessary in elusive cases [60,61]. Histopathology is characterized by reactive follicular hyperplasia and geographic microabscess formation representing necrotizing lymphadenitis [62].…”
Section: Cat Scratch Diseasementioning
confidence: 99%
“…Non-Hodgkin’s lymphoma) or infectious diseases (e.g. TbL or cat scratch disease [18]) or concurrent systemic lupus erythematosus (SLE). A recent study [19] reported 12% KFD patients had a history of SLE.…”
Section: Discussionmentioning
confidence: 99%